Determination of the most advantageous branching angle of the network of sections from the main pipelines - Makhanov M Маханов М (Рroblems of engineering and professional education, 2023)
The article considers the problems of determining the effective scheme at the stage of design and reconstruction of the system of branched and grouped water pipes.